О питании каменки рыжехвостой (Oenatithe xanthoprymna Hempr et Еhг.) в Бадахшане - Лоскот, В.М.; Петрусенко, А.А. (Вестник зоологии, 1974)
The data on distribution and quantity of Oenanthe xanthoprymna Hempr. et Ehr. in different biotopes of Badakhshan (the Tajik SSR) are given in the article. Nutrition of adult birds and nestlings in spring-summer period was analysed. In the ration of this species the following insects were predominant: Coleoptera, Hymenoptera, Hemiptera and caterpillars of Lepidoptera mainly the phytophagous pests.